2018
DOI: 10.1007/s00381-018-3860-4
|View full text |Cite
|
Sign up to set email alerts
|

Short versus mid-long-term outcome of transanal irrigation in children with spina bifida and anorectal malformations

Abstract: We observed a sustained improvement in bowel management and quality of life in SB and ARM children during the study, more significant in the short term than in mid-long term. To maintain success rates in the mid-long term and to reduce the dropout rate, we propose patient training and careful follow-ups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 29 publications
1
44
0
9
Order By: Relevance
“…Twelve studies reported interventions using medically assisted techniques that focused solely on faecal continence. 38,55,58,59,[61][62][63][64]70,71,74,77,78,80,85,90 Seven studies looked at the use of transrectal or transanal irrigation (TAI) to improve faecal continence. Both of these interventions are the same and involve the irrigation of the rectum and lower colon using fluid inserted via a catheter that is passed through the anus into the rectum.…”
Section: Medically Assisted Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies reported interventions using medically assisted techniques that focused solely on faecal continence. 38,55,58,59,[61][62][63][64]70,71,74,77,78,80,85,90 Seven studies looked at the use of transrectal or transanal irrigation (TAI) to improve faecal continence. Both of these interventions are the same and involve the irrigation of the rectum and lower colon using fluid inserted via a catheter that is passed through the anus into the rectum.…”
Section: Medically Assisted Techniquesmentioning
confidence: 99%
“…One study 70 focused on transrectal irrigation (TRI); the majority (35/40) of participants with spina bifida were still using TRI at follow-up and all participants were continent and free of constipation. Five studies focused on TAI using Peristeen; [62][63][64]78,85,90 Two studies 58,71 reported the outcomes of interventions using anal plugs in 18-20 children and young people with spina bifida aged 4-29 years. Both studies reported overall improvements in patientreported outcomes relating to the impact of faecal incontinence on daily life.…”
Section: Medically Assisted Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the introduction of a revised method of transanal irrigation (TAI) [8], many children were treated surgically with a Malone antegrade continence enema [7] or colostomy. TAI has transformed the management of NBD, and now is widely used in adults and children with SB [9][10][11][12]. Thanks to the improved survival of children with neurological conditions that were previously considered fatal, and better awareness and diagnostic techniques, the worldwide population of children and adolescents with NBD is growing.…”
Section: Introductionmentioning
confidence: 99%
“…In the decade since, multiple authors have discussed the utility of emptying the colon mechanically with antegrade enemas or trans-anal (retrograde) irrigations [5][6][7]. This practice allows the colon to be mechanically cleaned and with the goal to prevent incontinence episodes until stool moves around to the rectum, which is then emptied with a subsequent enema or flush.…”
Section: Introductionmentioning
confidence: 99%